Relations between Creativity, Education and Job Experience in Municipal Company in Poland - Marek JABŁOŃSKI; Jakub BARTAK; Łukasz JABŁOŃSKI (Communications of International Proceedings, 2021)
Paper aims at investigation of interdependence between work creativity, education and job experience of employees i.e. the change in number of particular types of jobs (nonroutine cognitive, routine cognitive, nonroutine manual, routine manual) representing different level of creativity and its interdependence with level education and job experience of employees of one of the municipal company operating in Poland. Study employs firm-level data covering over 2.200 observations obtained from two time periods, which are 2009 and 2018. The research proceedings were based on document analysis, structured interviews, team work methods, and classification technique. Having employed the firm-level data, it was found that the share of employees who performed more creative tasks increased. Moreover these employees represented relatively higher educational level. The relatively shorter average job experience (total and within company) was noted for employees performing cognitive work. Although, the average job experience in the group of employees performing routine manual and non-routine cognitive work was increased.
Keywords: Creativity; Experience; Education; Municipal Company.